Real-world derived weight-based levothyroxine doses to achieve optimal thyrotropin target in different degrees of autoimmune hypothyroidism - Tamer Mohamed Elsherbiny (SpringerOpen, 2024)
Abstract Purpose All patients with overt and severe subclinical hypothyroidism (SCH), and some with mild SCH require levothyroxine (L-T4) therapy. The present study aims to report real-world derived weight-based L-T4 doses to achieve optimal-low normal-thyrotropin target in different degrees of autoimmune hypothyroidism. Methods This was a retrospective study of patients with autoimmune hypothyroidism. Inclusion criteria were consistent achievement of optimal TSH target (0.3 to 2.5 µIU/L) using a stable L-T4 dose for at least 6 months. Patients were classified into 4 groups: group 1; mild SCH, group 2; severe SCH, group 3; overt hypothyroidism, and group 4; hypothyroidism with unknown initial TSH and free T4. Weight-based L-T4 doses were calculated for each group. Results Eighty-seven, 95, 75, and 91 patients met the inclusion criteria for groups 1-4, respectively. Weight-based L-T4 dose was the lowest in group 1 (1 ± 0.25 µg/kg/day), was the highest in group 3 (1.4 ± 0.29 µg/kg/day), while in groups 2 (1.2 ± 0.26 µg/kg/day), and 4 (1.2 ± 0.31 µg/kg/day) were not statistically different from each other. There was a significant decrease in weight-based L-T4 dose with increasing body weight categories in groups 1 and 2, and a significant difference between those less than 60 or ≥ 60 years of age in group 3. Conclusion Real-world derived weight-based L-T4 doses to achieve optimal TSH target are 1, 1.2, and 1.4 µg/kg/day for patients with mild, severe SCH, and overt autoimmune hypothyroidism, respectively. Age and body weight subcategories can better fine-tune required doses.